2014
DOI: 10.5144/0256-4947.2014.508
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization of unusual cystic echinococcosis in southern part of Turkey

Abstract: BACKGROUND AND OBJECTIVESThe incidence of primary extrahepatic cystic echinococcosis (CE) is rare. Generally, radiological and serological findings can help establish the diagnosis of hepatic and pulmonary CE, but a CE in an unusual location with atypical radiological findings may complicate the differential diagnosis. The objective of this study is to present the characteristics of cases with extrahepatic CE in respect of sites of involvement, clinical presentations, radiological findings, serological diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…In a series with 661 cases Akcam et al reported unusual localizations in 20% with breast CE in 0.15% (n=1). 33 Depending on the developmental stage, the cysts may mimic simple cysts, fibroadenoma, phylloides tumor, inflammatory cancer, mastitis, abscess or rare mammary abnormalities, which should be included in the differential diagnosis. 9,10,21,34 Distribution of cases by country.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a series with 661 cases Akcam et al reported unusual localizations in 20% with breast CE in 0.15% (n=1). 33 Depending on the developmental stage, the cysts may mimic simple cysts, fibroadenoma, phylloides tumor, inflammatory cancer, mastitis, abscess or rare mammary abnormalities, which should be included in the differential diagnosis. 9,10,21,34 Distribution of cases by country.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,21,34 Distribution of cases by country. Turkey 2,5,7,12,17,18,22,33,34,[37][38][39]45,[47][48][49][50][51][52][53][54] , Israel 55 , Jordan 23,56 , Saudi Arabia 36,57 , Iran 24,25 , Afghanistan 25,58 , Pakistan 8,11,59,60 , India 9,10,13,16,26,40,44,46,[61][62][63][64][65][66][67][68]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thyroid localization of HC remains unusual, even in the series of highly endemic countries for this Parasitosis; in fact, no case of HC of the thyroid gland was found in the Tunisian series of Bellil S, et al [3] of 265 operated extra pulmonary HC, in the Iranian series of Vahedi MA et al of 318 patients operated for HC [5], in the Turkish series of Gun E [6] of 329 cases of HC collected over 10 years with 72 cases of unusual localizations, and in the Greek series of Lianos GD et al of 233 cases of HC with 18 Unusual locations [11]. Only one case of thyroid HC was noted in the Akcam AT, et al [12]. Turkish series of 661 operated HC including 134 of unusual localization (0.15%) and a single case was also noted in Çakir M, et al [8] series of 157 HC of unusual localization (0.6%).…”
Section: Discussionmentioning
confidence: 99%
“…The method provides extra strength of lung parenchyma and prevents subsequent dissemination through air and formation of empyema. 17 , 18 …”
Section: Discussionmentioning
confidence: 99%